Estudio palinológico de los 35 mts. superiores de la sección tarragona, sabana de bogotá (1979)
In this study it is given the result of the palynological study of the uppermost 35 meters of the Tarragona section, located in the Sabana de Bogotá at an altitude of 2.560 meters above sea level.  It is described: 2 genus (Spirotremesporites, Striadyadosporites) and 5 species (Spirotremesporites simplex, Spirotremesporites multiplex, Spirotremesporites ecuatorialis, Striadyadosporites elongatus and Striadyadosporites constrictus) of fossil fungi, 14 types of pollen, 8 types of trilete spores, 4 types of Pediastrum and one special type of Chlorococcales.  On the basis of the relation, Pollen of paramo elements to Pollen of forest elements (Pp/Pb) and the stratigraphy it was possible to divide the pollen diagram in 8 climatic zones (vegetation); with them, it was possibleto correlate the Tarragona section with another sections carried out in the Sabana de Bogotá and surrounding areas. With this correlation and the absolute ages from the different sections of the area, it was possible to make a tentative correlation with the european cronostratigraphyc units. The uppermost 35 meters of the Tarragona section represents the geologicalhistory at least of the last 500.000 years of the Sabana de Bogotá.